Late ventricular septal defect due to blunt trauma - Hassan Soleimanpour; Samad Shams Vahdati; M.Bassir A.Fakhree (BioImpacts, 2015)
Introduction: This is very rare case report regarding late ventricular septal defect (VSD) following blunt trauma. Case Report: A 23-year-old motorcycle rider lost control and crashed to another motorcycle. He was transferred to emergency department by emergency medical services. Initial evaluation revealed some minor trauma which was managed, and he was discharged. There was a lately developed large apical VSD with delayed cardiopulmonary deterioration. The defect was recognized more than 10 days after accident, and repaired the day after. Discussion: Most VSD patients with blunt trauma remain asymptomatic following trauma while those with no primary findings experience gradual decompensation.